Downwearing rates on shore platforms of different calcareous lithotypes - Moura, D. (2019)
Vertical lowering (downwearing) of shore platform surfaces is a very important mechanism in their morphological evolution albeit much remains incompletely understood. The efficacy of mechanical and chemical weathering acting on a given substrate, together with erosional processes, influences downwearing rates. In order to determine the relationship between lithotypes and downwearing rates, data collected from a Transverse Micro-erosion Meter were obtained for shore platforms of three different calcareous lithotypes (biocalcarenite, calcarenite and carbonated siltstone) along the central Algarve coast (Southern Portugal). Downwearing rates ranged between 0.096 mm year−1 and 1.676 mm year−1 in biocalcarenite and weakly cemented calcarenite, respectively. In addition, physical properties of the rocks comprising the platforms were measured, including uniaxial compressive strength (as determined by the Point Load Test), porosity, and calcium carbonate content. The results show that downwearing depends primarily on the intrinsic properties of the substrate. Porosity, in particular, acts in two ways: (i) it tends to weaken the substrate; and, (ii) it controls the downward extent of the water percolation and therefore the depth of the weathering mantle subject to erosion by waves and currents.